2021
DOI: 10.1002/hsr2.263
|View full text |Cite
|
Sign up to set email alerts
|

A whole of population retrospective observational study on the rates of polypharmacy in New Zealand 2014 to 2018 Polypharmacy in New Zealand: What is the current status?

Abstract: Background and Aims Polypharmacy (≥5 medicines) and hyperpolypharmacy (≥10 medicines) can significantly impact people's health. The literature surrounding polypharmacy focuses on the elderly, particularly rest home populations, with few studies looking into younger age bands. Moreover, there have been no recent studies looking into the rates of polypharmacy in New Zealand. This study aimed to determine whether polypharmacy rates have increased over time in the New Zealand population. Specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…However, little information exists in large-scale studies worldwide, with the adult population. In this study, a prevalence of polypharmacy of 10.5% was found, a value similar to studies from Poland and New Zealand, which recorded 11.7% and 9.9% of polymedicated individuals, respectively [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…However, little information exists in large-scale studies worldwide, with the adult population. In this study, a prevalence of polypharmacy of 10.5% was found, a value similar to studies from Poland and New Zealand, which recorded 11.7% and 9.9% of polymedicated individuals, respectively [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…We found a successful reduction in polypharmacy among the “75 years and above” subgroups, with a more than 16% reduction in PRR (long-term). A similar study in New Zealand reported a 1–2% reduction in polypharmacy prevalence in older adults between 2014 and 2018 [ 28 ]. The female subgroup showed an approximately 5% greater reduction in PRR (long-term) than the male subgroup.…”
Section: Discussionmentioning
confidence: 99%
“… 72 In Australasia, nationwide studies have also observed increases in polypharmacy prevalence. 48 , 78 , 79 Between 2005 and 2013, the proportion of New Zealanders aged ⩾65 years experiencing polypharmacy increased from 23.4% to 29.5% ( p < 0.001), 78 with similar increases in Australia between 2006 and 2014 (33.2–39.8%) among those aged ⩾70 years. 48 However, polypharmacy prevalence among Australians declined over the following 3 years to 36.2% by 2017, 48 with similar patterns of declining rates between 2014 and 2018 among older age groups (⩾60) in New Zealand.…”
Section: Polypharmacy (Overprescribing)mentioning
confidence: 99%
“… 48 However, polypharmacy prevalence among Australians declined over the following 3 years to 36.2% by 2017, 48 with similar patterns of declining rates between 2014 and 2018 among older age groups (⩾60) in New Zealand. 79 While this suggests we may be seeing translational outcomes for the efforts made to reduce unnecessary polypharmacy among older adults, during the same time frame (2014–2018) the prevalence of New Zealanders aged 20–29 taking ⩾5 medicines increased by 30.4%. 79 This highlights the potential importance of broadening research to investigate polypharmacy among all adult age groups.…”
Section: Polypharmacy (Overprescribing)mentioning
confidence: 99%
See 1 more Smart Citation